The relationship of ambience and interaction experiences towards customer satisfaction: case of water park visitors in Bali - Handayani, Diah Badriah; Sugandi, Gagan; Razak, Anis Abd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to measure the relationship between ambience and interaction towards customer’s satisfaction in a unique setting which is water park. Water park is known as a place where customer come to enjoy and have fun. The question is whether it is important to invest on the ambience that could be not associate to the ultimate purpose of customer who come to the water park. Second objective is to validate the role of customer interactions towards customer satisfaction. Data were collected from 200 customers at the exit section. Only customer who exit from the water park is eligible to participate. One of the reason is because only customer who experiences the water park can help to give feedback based on their involvements. The results indicate that both ambience and customer interactions are positively related towards customer satisfaction. Customer is always expecting the best services from the service providers regardless the nature of services offered to them. The results of the study is only limited to the case of Bali, Indonesia and it may need a further validation in other part of the world. The study establishes the need to manage customers’ ambience and customer interactions experiences in water parks.• Adnyana;, , & Sri Darma, G. (2015). Strategi Marketing Mix, Yield Management, Customer Satifaction and Occupany Rate. Jurnal Manajemen Dan Bisnis.• Amin, A., Al-Obeidat, F., Shah, B., Adnan, A., Loo, J., & Anwar, S. (2019). Customer churn prediction in telecommunication industry using data certainty. Journal of Business Research, 94(February 2018), 290–301. https://doi.org/10.1016/j.jbusres.2018.03.003• Aziz, A., Ariffin, A. A. M., Omar, N. A., & Evin, C. (2012). Examining the impact of visitors’ emotions and perceived quality towards satisfaction and revisit intention to theme parks. Jurnal Pengurusan. https://doi.org/10.17576/pengurusan-2012-35-09• Ballantyne, , & Varey, R. J. (2006). Creating value-in-use through marketing interaction: The exchange logic of relating, communicating and knowing. Marketing Theory. https://doi.org/10.1177/1470593106066795• Berry, L., Parasuraman, A., & Zeithaml, V. A. (1985). The Service-Quality Puzzle.• Borishade, , Kehinde, O., Iyiola, O., Olokundun, M., Ibidunni, A., Dirisu, J., & Omotoyinbo, C. (2018). Dataset on customer experience and satisfaction in healthcare sector of Nigeria. Data in Brief, 20, 1850–1853.• Djumarno, Anjani, , & Djamaluddin, S. (2018). Effect of Product Quality and Price on Customer Loyalty through Customer Satisfaction. International Journal of Business and Management Invention (IJBMI).• Gallarza, G., Arteaga, F., & Gil-Saura, I. (2019). Customer value in tourism and hospitality: Broadening dimensions and stretching the value-satisfaction-loyalty chain. Tourism Management Perspectives, 31(February), 254–268. https://doi.org/10.1016/j.tmp.2019.05.011• Grönroos, C. (2011). A service perspective on business relationships: The value creation, interaction and marketing interface. Industrial Marketing Management, 40(2), 240–247. https://doi.org/10.1016/j.indmarman.2010.06.036• Hall, Z. R., Ahearne, M., & Sujan, H. (2015). The importance of starting right: The influence of accurate intuition on performance in Salesperson-Customer interactions. Journal of Marketing. https://doi.org/10.1509/jm.13.0505• Hassan, , & Shamsudin, M. F. M. F. (2019). Measuring the effect of service quality and corporate image on student satisfaction and loyalty in higher learning institutes of technical and vocational education and training. International Journal of Engineering and Advanced Technology, 8(5), 533–538. https://doi.org/10.35940/ijeat.E1077.0585C19• Hirata, (2019). Service characteristics and customer satisfaction in the container liner shipping industry.Asian Journal of Shipping and Logistics, 35(1), 24–29. https://doi.org/10.1016/j.ajsl.2019.03.004• Huang, C. (2017). The impacts of brand experiences on brand loyalty: mediators of brand love and trust.Management Decision, 55(5), 915–934. https://doi.org/10.1108/MD-10-2015-0465• Kadir, , & Shamsudin, M. F. (2019). A case study analysis of typhidot: An example of market-oriented R & D commercialization in Malaysia. International Journal of Financial Research, 10(5), 75–81. https://doi.org/10.5430/ijfr.v10n5p75• Kadir, Baharudin, Shamsudin, M. F., Nurul, I., & Mohd, H. (2020). Relevance of Blank ’ s Customer Development Model in Selected Cases of Market-Oriented R & D Commercialization in Malaysia. Test Engineering & Management, (4256), 4256–4259.• Kim, J. (2012). The dimensionality of fashion-brand experience: Aligning consumer-based brand equity approach. Journal of Fashion Marketing and Management, 16(4), 418–441. https://doi.org/10.1108/13612021211265827• Kim, H., Cho, J. L., & Kim, K. S. (2019). The relationships of wine promotion, customer satisfaction, and behavioral intention: The moderating roles of customers’ gender and age. Journal of Hospitality and Tourism Management, 39(October 2018), 212–218. https://doi.org/10.1016/j.jhtm.2019.03.001• Kotler, (1992). Marketing’s new paradigms: What’s really happening out there. Planning Review, 20(5), 50–52. https://doi.org/10.1108/eb054382• Legendre, T. S., Cartier, E. A., & Warnick, B. (2019). The impact of brand experience on the memory formation. Marketing Intelligence and Planning, 38(1), 15–31. https://doi.org/10.1108/MIP-02-2019-0109• Lindgreen, A., Palmer, R., & Vanhamme, J. (2004). Contemporary marketing practice: Theoretical propositions and practical implications. Marketing Intelligence & Planning, 22(6), 673–692. https://doi.org/10.1108/02634500410559051• Liu, Y., Song, Y., Sun, J., Sun, C., Liu, C., & Chen, X. (2019). Understanding the relationship between food experiential quality and customer dining satisfaction: A perspective on negative bias. International Journal of Hospitality Management, (September), 102381. https://doi.org/10.1016/j.ijhm.2019.102381• Mattila, S., & Ro, H. (2008). Customer satisfaction, service failure, and service recovery. In Handbook of Hospitality Marketing Management (Sixth Edit). https://doi.org/10.1016/b978-0-08-045080-3.50014-7• Milman, A., Okumus, F., & Dickson, D. (2010). The global theme park industry. Worldwide Hospitality and Tourism Themes, 2(3), 220–237. https://doi.org/10.1108/17554211011052177• Muhammad, I., Farid Shamsudin, M., & Hadi, N. U. (2016). How Important Is Customer Satisfaction? Quantitative Evidence from Mobile Telecommunication Market. International Journal of Business and Management, 11(6), 57. https://doi.org/10.5539/ijbm.v11n6p57• Nayeem, T., Murshed, F., & Dwivedi, A. (2019). Brand experience and brand attitude: examining a credibility-based mechanism. Marketing Intelligence and Planning, 37(7), 821–836. https://doi.org/10.1108/MIP-11-2018-0544• Oliver, R. L. (1993). Cognitive, Affective, and Attribute Bases of the Satisfaction Response. Journal of Consumer Research, 20(3), 418. https://doi.org/10.1086/209358• Oliver, R. L., & Swan, J. E. (1989). Equity and Disconfirmation Perceptions as Influences on Merchant and Product Satisfaction. Journal of Consumer Research, 16(3), 372. https://doi.org/10.1086/209223• Parasuraman, A. A., Zeithaml, V. A., & Berry, L. L. (1991). Refinement and reassessment of the SERVQUAL instrument. Journal of Retailing, 67(4), 420–450.• Ramanathan, R., Di, Y., & Ramanathan, U. (2016). Moderating roles of customer characteristics on the link between service factors and satisfaction in a buffet restaurant. Benchmarking, 23(2), 469–486. https://doi.org/10.1108/BIJ-01-2015-0012• Razak, A. A. A., & Shamsudin, M. F. M. F. (2019). The influence of atmospheric experience on Theme Park Tourist’s satisfaction and loyalty in Malaysia. International Journal of Innovation, Creativity and Change, 6(9), 10–20.• Richardson, H. W., Park, J. Y., Gordon, P., Moore, J. E., & Pan, Q. (2014). Theme parks. In National Economic Impact Analysis of Terrorist Attacks and Natural Disasters. https://doi.org/10.4337/9781783475865.00008• Shamsudin, M. F. M. F., Ali, A. M. A. M., Wahid, R. A. R. A., & Saidun, Z. (2019). Factors influence undergraduate students’ decision making to enroll and social media application as an external Humanities and Social Sciences Reviews, 7(1), 126–136. https://doi.org/10.18510/hssr.2019.7116• Shamsudin, M. F. M. F., Esa, S. A. S. A., & Ali, A. M. A. M. (2019). Determinants of customer loyalty towards the hotel industry in International Journal of Innovation, Creativity and Change, 6(9), 21–29.• Shamsudin, F. M. F., Ishak, M. F. M. F., Hashim, M. A. M. A., Nabi, M. A. M. A., Yazid, M. F. M.• F. M., & Razak, A. A. A. A. (2019). Preliminary analysis on relationship of CRM functions implementation towards firm’s business performance. Humanities and Social Sciences Reviews, 7(1), 113–• https://doi.org/10.18510/hssr.2019.7114• Shamsudin, M. F., Nurana, N., Aesya, A., & Nabi, M. A. (2018). Role of university reputation towards student choice to private universities. Opcion, 34(Special Issue 16), 285–294.• Shamsudin, M. F., Razak, A. A., & Salem, M. A. (2018). The role of customer interactions towards customer satisfaction in theme parks experience. Opcion, 34(Special Issue 16), 546–558.• Shamsudin, M.F., Razak, A. A., & Salem, M. A. (2018). The role of customer interactions towards customer satisfaction in theme parks experience | El papel de las interacciones del cliente hacia la satisfacción del cliente en la experiencia de los parques temáticos. Opcion, 34(Special Is), 546–558.• Torres, E. N., Milman, A., & Park, S. (2018). Delighted or outraged? Uncovering key drivers of exceedingly positive and negative theme park guest experiences. Journal of Hospitality and Tourism Insights, 1(1), 65–85. https://doi.org/10.1108/jhti-10-2017-0011• Zhang, , Zhang, J., & Zhang, M. (2019). From free to paid: Customer expertise and customer satisfaction on knowledge payment platforms. Decision Support Systems, 127(March), 113140. https://doi.org/10.1016/j.dss.2019.113140